THE EFFECT OF PREGNANCY MASSAGE ON REDUCING BACK PAIN IN TRIMESTER PREGNANT WOMEN IN THE WORK AREA OF KAYEN PUBLIC HEALTH CENTER, PATI REGENCY - Siti Ni’amah; Sri Hadi Sulistiyaningsih (Lppm Unan, 2022)
Background; In the third trimester of pregnancy, there are physical and psychological changes. This condition causes pregnant women to experience complex complaints such as discomfort, one of which is back pain. One solution to overcome this discomfort is massage for pregnant women. This study aims to determine the effect of pregnancy massage on reducing back pain in trimester pregnant women in the work area of Kayen Public Health Center, Pati Regency. Methods: This type of research uses a pre-experiment - one group pre post test design. The study population was 30 pregnant women in the third trimester with a total sampling technique. The independent variable is massage in pregnant women and the dependent variable decreases back pain in pregnant women. Research instrument using SOP, data analysis using statistical test t test is equal to 0.819 with a probability value far below 0.05. Results: This study showed that before massage, 16 pregnant women (53.3%) experienced mild pain after massage. 25 pregnant women (83.3%) experienced mild pain and 5 pregnant women (16.7%) have moderate pain. Conclusion: there is an effect of massage for pregnant women on reducing back pain for pregnant women in the third trimester in the work area of the Kayen Health Center, Pati Regency